Optimizing Inclusion and Accessibility in Digital Education with Adaptive Learning - Riya Widayanti; Henry Zainarthur; Maulana Abbas (Jurnal MENTARI: Manajemen, Pendidikan dan Teknologi Informasi, 2026)
This study examines the persistent challenges in achieving inclusive and accessible digital education, particularly for learners with diverse abilities, varying levels of technological readiness, and different socio-economic backgrounds, despite rapid advancements in educational technology. It focuses on optimizing inclusion and accessibility through an adaptive digital education approach that responds to individual learner needs and specific learning contexts. A mixed-methods research design was employed, combining a quantitative survey administered to students and educators engaged in digital learning environments with qualitative interviews to 200 respondents capture in-depth experiential insights. Structural Equation Modeling (SEM) was utilized to analyze the relationships among adaptive learning features, accessibility, and inclusive learning outcomes. The findings demonstrate that adaptive digital education systems significantly enhance learning accessibility, learner engagement, and perceived inclusivity. Personalization mechanisms and adaptive content delivery emerged as the strongest contributing factors. Moreover, adaptive technologies were shown to reduce learning barriers for students with varying learning speeds and specific accessibility requirements. Overall, the study confirms that optimizing adaptive digital education is essential for fostering inclusive and accessible learning environments and underscores the need to integrate adaptive system design into educational policies and digital learning strategies to promote equitable educational opportunities across diverse contexts.